REDEFINING CONSUMER PROTECTION: A CRITICAL EVALUATION OF FAIRNESS AND JUSTICE IN MODERN TRADE TRANSACTIONS - Zulkifli; Nasrianti; Muhibuddin; Rahmaniar; Teuku Yudi Afrizal (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Consumer protection in trade transactions has become a critical issue in modern commerce, especially with the rise of digital transactions. Despite existing regulations, many consumers remain vulnerable to information asymmetry, exploitation, and injustice in trade. This article aims to critically evaluate the concept of justice in trade through the perspectives of human rights and public policy. The focus is on consumer protection in sale transactions, both in conventional trade and e-commerce, exploring how human rights principles and public policy can offer solutions to the injustices consumers face. This study employs a juridical-normative approach with a comparative analysis between Indonesian law and international human rights norms. Key legal frameworks such as the Indonesian Consumer Protection Law (No. 8/1999) and the Trade Law (No. 7/2014) are analyzed alongside the UN’s International Covenant on Economic, Social, and Cultural Rights (ICESCR). Primary data was collected through semi-structured interviews with 20 experts, e-commerce businesses, and consumers involved in digital trade transactions. Secondary data was derived from legal documents, consumer protection reports, and literature on Indonesian commercial law. The findings reveal that while Indonesia’s legal framework provides a foundation for consumer protection, its implementation remains inadequate, leaving consumers exposed to unfair practices in online transactions. The article suggests that consumer protection should not merely be a contractual formality but also a moral and ethical responsibility, ensuring consumers' rights to safety, fairness, and transparent transactions. From a human rights perspective, economic justice and social fairness are integral to consumer rights. The state has an obligation to ensure access to clear information, provide mechanisms for redress, and prevent exploitative practices in trade. Public policy must strengthen oversight, regulation, and consumer education in digital trade platforms, ensuring that they are transparent, fair, and provide accessible dispute resolution mechanisms. In conclusion, consumer protection in trade should be viewed not only through contractual agreements but also as part of economic justice, safeguarding consumers' rights to clear information, fair treatment, and the ability to seek compensation for harm. The state must play an active role in fostering a trade environment that aligns with human rights and effective public policy, creating a just and equitable marketplace.